Surgical Technique of Angiogenesis Stimulation (Extracardial Myocardial Revascularization) in Patients with Coronary Artery Disease - L, Shevchenko Yu; GG, Borshchev; DS, Ulbashev (Cardiology and Cardiovascular Medicine, 2022)
Background: Coronary artery disease (CAD) remains one of the main causes of morbidity, early disability, and mortality in the adult population, despite significant achievements in the diagnosis and treatment of coronary blood flow disorders. An undoubted achievement at the present stage is the improvement of conservative and X-ray endovascular treatment methods; however, this has led to an increase in the number of patients with diffuse coronary lesions. We have developed a method of combination treatment for CAD through direct myocardial revascularization (CABG) in combination with the method YurLeon, which improves the results in such patients. Materials and Methods: This study included 1,080 CAD patients with FC III–IV angina pectoris, who underwent surgical revascularization of the myocardium at Pirogov National Medical and Surgical Center, Russian Federation. A total of 650 men (60.19%) and 430 women (39.81%) aged 50 to 75 years were enrolled. Of them, 586 patients underwent coronary bypass surgery (CABG), whereas 494 patients underwent coronary bypass surgery supplemented with indirect revascularization using the YurLeon technique (CABG+YurLeon). Patients underwent gated-SPECT, echocardiography, computer tomography, coronary angiography and assessment of the quality of life using the SF-36 questionnaire. Results: At the intraoperative stage and in the early postoperative period, there were no significant differences in complication rates between the two groups (p>0.05). One year postoperatively, we observed statistically significant differences in functional class of angina pectoris (Me[Q1-Q3]): 2[1-2] (after CABG), 1[1-2] (after CABG+YurLeon); p<0,05; left ventricular ejection fraction (M±SD): 50.12±6.20% (after CABG), 56.10±5.81% (after CABG+YurLeon); p<0.05; rest extent